Yoneda completeness. (28th February 2017) - BICE, TRISTAN
Abstract : We characterize Yoneda completeness for non-symmetric distances by combinations of metric and directed completeness. One of these generalizes the Kostanek–Waszkiewicz theorem on formal balls.